Sleep Stage Classification via Ensemble and Conventional Machine Learning Methods using Single Channel EEG Signals - Ilhan, Hamza Osman; Bilgin, Gokhan (International Journal of Intelligent Systems and Applications in Engineering, 2017)
Sleep-stages play important roles in the diagnosis of the sleep disorders and the sleep-related illnesses. In this sense, accurate identification of the sleep-stages is a necessity for more robust and e client diagnosis systems. Several traditional machine-learning and pattern recognition algorithms are deployed on modern computer aided diagnosis systems. However, current results are not as satisfactory as expected. In the last two decade, a new concept has emerged with âensemble learningâ title. It has attracted the attention of many researchers from various disciplines. In this study, several ensemble-learning methods are utilized and inspected on EEG signals for sleep-stage classification. Conventional machine-learning methods are also performed in same testing phase to report comparative results. Additionally, methods are evaluated in two different scenarios; subject specific and independent. Study proves that combination of DTs and SVMs in Bagging theorem surpasses all of the conventional methods used in the experiments. Moreover, test trials reveal that both conventional and ensemble models need to be improved for subject independent scenario which is more essential case in the development of independent computer based diagnosis systems.